Development of Microcontroller-Based Ball and Beam Trainer Kit - Gunawan Dewantoro; Deddy Susilo; Ditya Clarisa Amanda (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
A ball and beam trainer kit based on microcontroller was developed for teaching control system course for the sophomore students. This specially-purposed kit consists of a ball located on a beam with a fixed axle at one of its end. At the other end, a servomotor was employed to control the position of the ball by adjusting the rotation angle of the servomotor. Seven predetermined positions were set to 10, 20, 30, 40, 50, 60, and 70 cm relative to the fixed axle of the beam. The Proportional-Integral-Derivative (PID) scheme was then used to compensate the error. This kit is equipped with a user interface to configure controller coefficients, select the set points, plot the actual ball position, and display parameter values. The user interface program runs on PC or notebook connected to microcontroller via serial communications. A questionnaire-based assessment about the use of this kit was conducted by 17 students taking the course, giving a rating value of 94.12%.